2015
DOI: 10.1016/j.sbspro.2015.01.780
|View full text |Cite
|
Sign up to set email alerts
|

School Principals’ Opinions on the FATIH Project in Turkey

Abstract: This study aims to determine the thoughts and opinions of the school principals on the FATİH Project initiated by the Ministry of Education to facilititate a technology-supported education in Turkey. 24 Principals were involved in the study. The answers of the principals received on structured interview forms that contained open-ended questions and were analysed with content analysis method. Results of the research show that a majority of the principals have positive opinion about the FATİH Project. The princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…According to Türel and Johnson (2012), teachers mostly avoided using IWBs during their lessons, but, if they did integrate IWBs into their experiences, most teachers used IWBs as overhead projectors and for Internet research. Research also identified the need for professional development for educators to integrate IWBs into their classrooms (Akkoyunlu & Baskan, 2015;Korkmaz & Cakil, 2013). Bourbour, Vigmo, and Samuelsson's (2015) study; Erbas, Ince, and Kaya's (2015) research; and Lopez and Krockover' ( 2014) study all concluded that IWBs were most useful if the educators knew how to utilize technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Türel and Johnson (2012), teachers mostly avoided using IWBs during their lessons, but, if they did integrate IWBs into their experiences, most teachers used IWBs as overhead projectors and for Internet research. Research also identified the need for professional development for educators to integrate IWBs into their classrooms (Akkoyunlu & Baskan, 2015;Korkmaz & Cakil, 2013). Bourbour, Vigmo, and Samuelsson's (2015) study; Erbas, Ince, and Kaya's (2015) research; and Lopez and Krockover' ( 2014) study all concluded that IWBs were most useful if the educators knew how to utilize technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interview also revealed that teachers are lacked of hands-on courses and workshop related to IS preparation and implementation. This view is also further supported by some researchers (Akkoyunlu & Baskan, 2015;Chapman & Mahick, 2004;Yang & Huang, 2008) claiming that lack of teacher training can challenge teachers to use certain technology in their lessons. The findings obtained also were aligned with the studies conducted ( Fig.…”
Section: Finding and Discussionmentioning
confidence: 84%
“…The interview also revealed that teachers are lacked of hands-on courses and workshop related to IS preparation and implementation. This view is also further supported by some researchers (Akkoyunlu & Baskan, 2015;Chapman & Mahick, 2004;Yang & Huang, 2008) claiming that lack of teacher training can challenge teachers to use certain technology in their lessons. The findings obtained also were aligned with the studies conducted (Ghavifekr & Wan Athirah, 2015; Tezci, 2011) in which they found that most teachers agree ICT integration is effective, but ICT facilities provided in school are not enough nor in good conditions.…”
Section: Research Questionmentioning
confidence: 86%